2015
DOI: 10.1186/s13000-015-0296-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of c-Met in breast cancer: a meta-analysis of 6010 cases

Abstract: BackgroundThe prognostic value of c-Met in breast cancer remains controversial. A meta-analysis of the impact of c-Met in breast cancer was performed by searching published data.MethodsPublished studies analyzing overall survival (OS) or relapse free survival (RFS) according to c-Met expression were searched. The principal outcome measures were hazard ratios (HRs) for RFS or OS according to c-Met expression. Combined HRs were calculated using fixed- or random- effects models according to the heterogeneity.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 44 publications
3
58
0
3
Order By: Relevance
“…For this group of patients, chemotherapy is the primary systemic therapy and there is a need for finding new targets for treatment. A prognostic role for Met in TNBC was likewise found in a meta-analysis study about Met [24]. Furthermore, it was found in the pre-menopausal cohort that stromal HGF, but not tumoural HGF, was associated with shorter survival from TNBC, a difference not previously reported.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For this group of patients, chemotherapy is the primary systemic therapy and there is a need for finding new targets for treatment. A prognostic role for Met in TNBC was likewise found in a meta-analysis study about Met [24]. Furthermore, it was found in the pre-menopausal cohort that stromal HGF, but not tumoural HGF, was associated with shorter survival from TNBC, a difference not previously reported.…”
Section: Discussionmentioning
confidence: 58%
“…In cohort 2, no correlation was found between MET gain and the HER2 positive subtype, which is in agreement with the meta-analysis conducted by Yan et al . [24]. Cohort 1, however, showed an association between MET gain and the HER2 positive subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the most common malignant tumor in women, and its incidence has been increasing year on year [1]. In addition, the age of breast cancer onset is decreasing [2].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that Met and EGFR are related to the more aggressive subtypes. Indeed, in concordance with other studies, MET and EGFR amplification was more frequently found in TNBC in the postmenopausal cohort [44,161,162]. MET gain was found to be correlated with the HER2-like subtype in the pre-menopausal cohort, in agreement with a 2013 study [163].…”
Section: Genes and Proteins In Relation To Clinicopathological Characsupporting
confidence: 80%
“…Contrarily, no correlation was found between MET gain and HER2-like disease in the postmenopausal cohort, which was likewise shown in a meta-analysis of multiple studies [162]. Interestingly, cytoplasmic pMet tended to be more abundant in the less- results [104].…”
Section: Genes and Proteins In Relation To Clinicopathological Characmentioning
confidence: 70%